Romani (Gipsy Caló) loanwords in Costa Rican Spanish - Portilla Chaves, Mario (2019)
This article analyzes the by Buzek (2013) Romani borrowings proposed appearing in Carlos Gagini’s dictionaries of 1893 and 1915. Furthermore, the author offers a wider list of them based on the review of several lexicographical works from Costa Rican Spanish published in the 20th century. Key Words: Romani; Gypsy language; borrowings; Costa Rican Spanish.